Penerapan Metode EDAS Dalam Pemilihan Wirausaha Muda Terbaik dengan Pembobotan ROC - Salmon Salmon; Bartolomius Harpad; Reza Andrea (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
An entrepreneur is a person or actor who has created a new business by taking on most of the risks that will occur and enjoying most of the rewards. Entrepreneurship aims to create or create a job field so that it can help another person's work and to train a job so as to create other people's welfare. A young entrepreneur is someone who is skilled in taking advantage of an opportunity to develop his business in order to improve life in a good direction. Young entrepreneurs should have criteria in running an entrepreneur such as: optimistic, innovative, creative and leadership. So the calculations from the research above use the Evaluation Based On Distance From Average Solution or EDAS method of weighting Rank Order Centroid (ROC) there are 10 alternatives and 4 criteria so that a higher decision value can be produced by Saiful (A1) first rank with value 1.